Changes in Motor Skill Performance of 13-Year-Old Japanese Boys and Girls: A Cross-Sectional Study over Six Decades (1964–2023) - Yukitomo Yogi (Sports)
This study examines six decades (1964–2023) of changes in motor skills and body dimensions among Japanese 13-year-old students, analyzing grip strength, handball throwing, 50 m dash, endurance running, and composite scores. National Physical Fitness and Motor Skills Survey data were analyzed alongside School Health Examination Survey measurements to identify trends and correlations between performance metrics and anthropometric variables. The results revealed distinct developmental patterns, with motor skills peaking in the 1980s for both genders, followed by decline until 2000, after which boys experienced stagnation while girls showed improvement until 2019. Both genders demonstrated marked decreases following 2020, coinciding with the COVID-19 pandemic. Notably, while height increased significantly over the study period, only boys’ 50 m dash performance showed strong positive correlations with height (r = 0.779) and BMI (r = 0.854). This longitudinal analysis demonstrates how interdisciplinary factors—including educational policy shifts, reduced physical education curriculum hours, changes in urban park design, diminished outdoor play opportunities, and increased sedentary behaviors—collectively impact children’s motor development. These findings hold significant implications for public health initiatives and sports education strategies aimed at reversing concerning trends in youth physical capabilities and addressing the substantial post-pandemic decline in motor performance.